2017
DOI: 10.1016/j.celrep.2017.09.081
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Genetically Intact HIV-1 Proviruses in Specific CD4 + T Cells from Effectively Treated Participants

Abstract: Summary Latent replication-competent HIV-1 persists in individuals on long-term antiretroviral therapy (ART). We developed the Full-Length Individual Proviral Sequencing (FLIPS) assay to determine the distribution of latent replication-competent HIV-1 within memory CD4+ T cell subsets in six individuals on long-term ART. FLIPS is an efficient, high-throughput assay that amplifies and sequences near full-length (~9 kb) HIV-1 proviral genomes and determines potential replication-competency through genetic charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

59
496
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 327 publications
(558 citation statements)
references
References 40 publications
59
496
3
Order By: Relevance
“…While it was originally believed by many that latently infected cells must be intrinsically long-lived, since cell division was expected to reactivate viral expression and lead to eventual cell death, a series of studies over the past few years have convincingly demonstrated that cells in the reservoir can proliferate while remaining latently infected (Reference 110,112). These studies have identified multiple latently infected cells -even in small samples -with virus integrated into identical sites [113][114][115] in the genome or with sequence-identical virus [116][117][118][119] -two findings that would be exceedingly unlikely to occur in two independent infection events and likely reflect division of infected cells.…”
Section: What Maintains the Latent Reservoir And How Can We Reducementioning
confidence: 99%
“…While it was originally believed by many that latently infected cells must be intrinsically long-lived, since cell division was expected to reactivate viral expression and lead to eventual cell death, a series of studies over the past few years have convincingly demonstrated that cells in the reservoir can proliferate while remaining latently infected (Reference 110,112). These studies have identified multiple latently infected cells -even in small samples -with virus integrated into identical sites [113][114][115] in the genome or with sequence-identical virus [116][117][118][119] -two findings that would be exceedingly unlikely to occur in two independent infection events and likely reflect division of infected cells.…”
Section: What Maintains the Latent Reservoir And How Can We Reducementioning
confidence: 99%
“…The ability of HIV‐1 to primarily infect CD4+ memory T cells, but also infect naive cells is further supported by recent studies of viral reservoirs. Studies examining intact proviral genomes and quantitative viral outgrowth assays (QVOA) have found that HIV‐1 can persist in naive and memory CD4+ T cells in ART‐treated individuals regardless of whether individuals initiate therapy during acute or chronic infection. However, it is worth noting that the percentage of naive cells harboring replication‐competent proviral genomes is typically lower than that of memory T cells .…”
Section: Introductionmentioning
confidence: 99%
“…Studies examining intact proviral genomes and quantitative viral outgrowth assays (QVOA) have found that HIV‐1 can persist in naive and memory CD4+ T cells in ART‐treated individuals regardless of whether individuals initiate therapy during acute or chronic infection. However, it is worth noting that the percentage of naive cells harboring replication‐competent proviral genomes is typically lower than that of memory T cells . The fact that naive cells are less likely to be latently infected after a period of ART may be due to them being less susceptible to infection prior to therapy or due to them turning over more rapidly after the initiation of therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Several recent studies have revealed important features of persistent HIV-1 that directly impact our understanding of the latent reservoir. Full viral genome sequencing studies have shown that over 93% of proviruses in resting CD4 + T cells in HIV + individuals on cART are defective (Ho et al 2013; Bruner et al 2016; Imamichi et al 2016; Hiener et al 2017; Lee et al 2017). These defective proviruses contain large internal deletions and/or hypermutation mediated by APOBEC3G, a host enzyme that deaminates dC to dU on the minus strand of HIV-1 cDNA during reverse transcription (resulting in a G to A hypermutation).…”
Section: A Historical Perspectivementioning
confidence: 99%